American recent Eulipotyphla Nesophontids, Solenodons, Moles, and Shrews in the New World - Woodman, Neal (Smithsonian contributions to zoology, 2018)
"The mammalian taxonomic order Eulipotyphla comprises the living families Erinaceidae (gymnures, hedgehogs, and moonrats), Solenodontidae (solenodons), Soricidae (shrews), and Talpidae (desmans and moles), as well as the recently- extinct Nesophontidae (nesophontids). Morphological and molecular studies continue to alter our view of relationships within and among these families, and this research has added considerably to our understanding of the diversity, distributions, and relationships of many of the New World (i.e., North and South America and associated islands) species that comprise them. Currently, there are more than 450 recognized living species worldwide, making the Eulipotyphla the third most speciose order of mammals. In this work, I attempt to summarize the taxonomic results of recent studies, provide a guide to the most appropriate current applications of New World taxonomic names and their synonyms, and indicate current understanding of their distributions. The eulipotyphlans of this region currently include 111 recognized species of shrews, seven species of moles, and both living species of solenodons."...Provided by publisher